Dinâmica populacional do caranguejo Austinixa aidae righi, 1976 (Brachyura: Decapoda: Phinnoteridae) em uma praia estuarina amazônica - ELERES, Wesley Thiago dos Santos (2024)
The objective of this work was to analyze the population structure of the Austinixa aidae crab on a beach of the Amazon coast. For that, samplings were carried out from October 2015 to April 2016, on Farol Velho beach (Salinópolis/PA) based on three 10m transects perpendicular to the line of the beach, in which 10 crab samples were obtained by transect using a suction pump that was used in the galleries of the kalassinid Lepidophthalmus siriboia. A total of 210 individuals were sampled, 105 juveniles, 42 males and 63 females, which among then 21 were ovigerous. An anomalous pattern of sex ratio was found (M:F = 0.67:1.0) which differed significantly from the expected ratio (1:1). Austinixa aidae exhibited a high number of individuals per gallery (1.0) and a high overall incidence per gallery (62%), suggesting that the studied beach is a favorable environment for this organism. The presence of ovigerous and juvenile females during all months sampled suggests continuous reproduction of this population. Comparing the results of this work with studies of A. aidae on beaches in southeastern Brazil, it is possible to observe evident differences between the population parameters, suggesting a latitudinal pattern for the species.